ANALISIS PERTUMBUHAN EKONOMI INDONESIA ANTARA TAHUN 2002-2008 (Panel Data Analisis: Studi Pada 6 Kepulauan Besar Di Indonesia) - Teddy C. Leasiwal (Soso-Q : Jurnal Manajemen, 2017)
The research was to find and analyze the determinants and the effect on Indonesia's Economic Growth and Economic Growth in 6 (six) Big Island in Indonesia by using: (i) Expansion of the Solow-Swan model and endogenous growth models, adding a factor of Education (PDDK), Sector Utilization Potential (PSP), (ii) as well as some factors that become sources of economic growth in Indonesia, the Foreign Direct Investment (FDI), Political Stability and Security (STAB). In contrast to previous studies that use a lot of cross section data or time series data covering several countries including Indonesia, in this study all data using the data per province to measure its impact on economic growth in each major island, with the approach of General Least Square (GLS ), during the period 2002-2008. Keywords: Economic Growth, Foreign Direct Investment, Education Sector Utilization Potential, Political Stability and Security, General Least Square